(untitled) (Revista Argentina de Musicología, 2012)
Faced with the adverse effects of modernity at the end of the 19th century, the intellectual élite of Buenos Aires argued against ‘moral materialism’ with arguments responding to an ‘aesthetic culture’. In this context, some writers and artists created the Ateneo and organized a series of orchestral concerts directed by Alberto Williams, the first of which was the Wagner Festival. This article analyzes a letter from Miguel Cané about that festival, published in the journal La Nación in 1894. This paper aims to explain how it manifests, justifies, and embodies a cultural position in which were aligned Cané as an intellectual, the Ateneo as an institution, Alberto Williams as an artist and the Festival as aesthetic statement. The letter can be read as an ideological stance: ‘aesthetic spiritualism’ and an aesthetic program against ‘moral materialism’. Discourse analysis is based on three aspects: the subject of énonciation, the regularities of speech and the argumentation.